Vygotsky and Literacy Research A Methodological Framework - Smagorinsky, Peter; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
In this book Peter Smagorinsky reconsiders his many publications employing Vygotsky$1 (Bs theory of culturally-mediated human development and applies them, through a unified and coherent series of chapters, to literacy research. This exploration takes previously-published work and incorporates it into a new and sustained argument regarding the application of Vygotsky$1 (Bs ideas to current questions regarding the nature of literacy and how to investigate it as a cultural phenomenon that contributes to human growth in social context. To conduct this inquiry, Smagorinsky first provides an overview that contextualizes Vygotsky both in his own time and in efforts to extrapolate from his Soviet origins to the 21st Century world. This consideration includes attention to the current context for literacy studies. He then reviews current conceptions of literacy in the realms of reading, writing, and additional tool use, grounding each in a Vygotskian perspective. The book$1 (Bs final chapters take a critical look at both research method and the writing of research reports, taking into account both research and research reports as social constructions based in disciplinary practices. On the whole, this volume makes an important contribution to Vygotskian studies and literacy research through the author$1 (Bs careful alignment between theory and practice.s
Keywords: Education; Literacy; Education; Literacy